PENYITAAN BARANG BUKTI YANG DILAKUKAN OLEH PENYIDIK POLRI DAN PROBLEMATIKANYA DALAM PRAKTEK - Sudarman Sudarman (Journal of Law ( Jurnal Ilmu Hukum ), 2017)
ABSTRACTThe process or procedure of seizure of evidence in a criminal case is as follows: Before performing its duties, the officer or investigator is required to obtain prior permission from the Chairman of the local District Court except in a very urgent and urgent circumstance; Showing his / her identification to the person from whom it was confiscated; The Authority shall instruct the person who controls the object to be confiscated to be handed over to the letter or writings of the suspect, shown to him, his or hers or destined for him, or a means of committing a crime; Shows objects to be confiscated to persons from whom they were seized or their families and marks of the merchandise witnessed by the village chief or the neighborhood leader with two witnesses; Creating news of foreclosure events, once read out and dated, signed by the investigator, the person concerned or his or her family and two witnesses; Before the seized items or goods are inserted in the confiscated storage house of the state, it shall first be noted about the weight or amount according to its kind, the characteristic or characteristic of the object, the place, the day and date of the seizure, the identity of the object it is confiscated and then wrapped, given lag and stamp of office and signed by the investigator; For the sake of security if deemed necessary to shoot first.Some of the obstacles encountered by the investigator in confiscating include: Evidence is no longer intact or damaged; Evidence is transferable to others; Evidence goes into another unity; Evidence is made of collateral in the Pawnshop; Missing evidence was not found. Efforts by the investigator to overcome these obstacles include: If the evidence is transferred to another person, then make D.P.O (List of People Search) or D.P.B (List of Goods Search) sent to POLDA; If the evidence enters another entity, then approach the Dankesatuan where the evidence is located, by ordering a person to purchase the evidence in the hope that the evidence may come out of the unitary territory and be used as evidence; If the evidence is mortgaged, then the Police confiscate the evidence by requesting the seizure approval to the District Court with the provisions of the District Court, only the pawnshop submits the evidence, although it must be argued; If missing evidence is not found, the investigator conducts a re-investigation at T.K.P (Place of Case Events); Seek testimony of witnesses and suspects by collecting witnesses and suspects to search for truths of evidence that are no longer shaped like jewelry that has been melted by the buyer.